Prism adaptation in the healthy brain: The shift in line bisection judgments is long lasting and fluctuates - Schintu, Selene; Pisella, Laure; Jacobs, Stéphane; Salemme, Romeo; Reilly, Karen T.; Farnè, Alessandro (Neuropsychologia, 2014)
Rightward prism adaptation has been shown to ameliorate visuospatial biases in right brain-damaged patients with neglect, and a single session of prism adaptation can lead to improvements that last up to several hours. Leftward prism adaptation in neurologically healthy individuals induces neglect-like biases in visuospatial tasks. The duration of these effects in healthy individuals, typically assumed to be ephemeral, has never been investigated. Here we assessed the time-course of the adaptation-induced modifications in a classical perceptual line bisection task that was repeatedly administered for approximately 40min after a single session of adaptation to either a leftward or rightward prismatic deviation. Consistent with previous reports, only adaptation to leftward-deviating prisms induced a visuospatial shift on perceptual line bisection judgments. The typical pattern of pseudoneglect was counteracted by a rightward shift in midline judgments, which became significant between 5 and 10min after adaptation, fluctuated between being significant or not several times in the 40min following adaptation, and was present as late as 35min. In contrast, the sensorimotor aftereffect was present immediately after adaptation to both rightward and leftward deviating prisms, decayed initially then remained stable until 40min. These results demonstrate that both the sensorimotor and visuospatial effects last for at least 35min, but that the visuospatial shift needs time to fully develop and fluctuates. By showing that the effects of prism adaptation in the undamaged brain are not ephemeral, these findings reveal the presence of another, so-far neglected dimension in the domain of the cognitive effects induced by prism adaptation, namely time. The prolonged duration of the induced visuospatial shift, previously considered to be a feature of prism adaptation unique to brain-damaged subjects, also applies to the normal brain. •Leftward prism adaptation induces a long-lasting visuospatial shift.•This shift in line bisection judgments takes time to develop fully.•This shift lasts at least 35min and fluctuates across time.